2022
DOI: 10.1186/s43141-022-00365-w
|View full text |Cite
|
Sign up to set email alerts
|

Assessment of simple sequence repeats signature in hepatitis E virus (HEV) genomes

Abstract: Background Hepatitis E virus (HEV) is small (27–34 nm diameter) non-enveloped with positive sense ssRNA genome. Microsatellites or simple sequence repeats (SSR) are short tandem repeat sequences present across coding and non-coding regions of both prokaryotes and eukaryotes. They are involved with genome function and evolution at multiple levels. Results The complete genome sequences of 22 HEV genomes of the family Hepeviridae and genus Orthohepevi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5

Relationship

1
4

Authors

Journals

citations
Cited by 6 publications
(4 citation statements)
references
References 22 publications
0
4
0
Order By: Relevance
“… Laskar et al (2021) , ( 2022 ), Jilani and Ali (2022) used similar information about incidence, prevalence, composition, and localization in their studies of Simple Sequence Repeats Signature in viruses using IMEx. Those analyses might seem basic, but they require a lot of data tabulation before the tables are ready for analysis, a feature that is already automated by EasySSR.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“… Laskar et al (2021) , ( 2022 ), Jilani and Ali (2022) used similar information about incidence, prevalence, composition, and localization in their studies of Simple Sequence Repeats Signature in viruses using IMEx. Those analyses might seem basic, but they require a lot of data tabulation before the tables are ready for analysis, a feature that is already automated by EasySSR.…”
Section: Resultsmentioning
confidence: 99%
“…It is possible to notice that when mismatches were allowed in a tract, EasySSR through the IMEx algorithm could extend tracts that were previously interrupted by an imperfection and considered as perfect because it had passed the repetition cutoff when they were actually part of longer imperfect tracts; thus, the average amount of perfect SSRs per genome decreased from 53.5 to 40 in the analysis that included imperfections. Laskar et al (2021Laskar et al ( ), (2022, Jilani and Ali (2022) used similar information about incidence, prevalence, composition, and localization in their studies of Simple Sequence Repeats Signature in viruses using IMEx. Those analyses might seem basic, but they require a lot of data tabulation before the tables are ready for analysis, a feature that is already automated by EasySSR.…”
Section: 23mentioning
confidence: 99%
“…In terms of motif composition of SSRs, we observed that found all the mono-nucleotide SSRs were almost exclusively localized to the A/T region. This is significant because when viruses have human and related hosts, the mono-nucleotide SSRs are either exclusively or predominantly present in the A/T region of the genome irrespective of the genome GC% [15] , [16] , [17] . Amongst the di-nucleotide repeats motif, AT/TA has high prevalence of 63% which can serve as hotspots for mutation and genome evolution [29] , [30] .…”
Section: Discussionmentioning
confidence: 99%
“…They have greater role (10–100-fold) in mutation in coding region than another part of genomic region [13] . The pattern and distribution of SSRs has also been used as marker for speciation, host divergence and evolution [14] , [15] , [16] , [17] , [18] , [19] .…”
Section: Introductionmentioning
confidence: 99%